2007
DOI: 10.1007/s10620-006-9696-x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytapheresis (LCAP) in the Management of Chronic Active Ulcerative Colitis—Results of a Randomized Pilot Trial

Abstract: Recent studies suggest that leukocytapheresis with Cellsorba is a valuable therapy for ulcerative colitis after failure of conventional treatment. In this study the potential of leukocytapheresis to induce remission in refractory chronic colitis under the conditions of European treatment guidelines was investigated. The therapeutic benefit of leukocytapheresis in the maintenance of remission was additionally elucidated. Twenty patients were treated weekly for 5 weeks. A significant decrease in the activity ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
2
15
0
2
Order By: Relevance
“…The indication has been treatment of mild to moderate attacks of UC with high response and remission rates, enabling lower steroid dosage [5,6]. One important advantage is the lack of significant adverse events [7], which can sometimes be encountered with potent immunomodulatory or immunosuppressive pharmaceutical compounds such as anti-TNF agents [8] or thiopurine agents [9].…”
Section: Introductionmentioning
confidence: 99%
“…The indication has been treatment of mild to moderate attacks of UC with high response and remission rates, enabling lower steroid dosage [5,6]. One important advantage is the lack of significant adverse events [7], which can sometimes be encountered with potent immunomodulatory or immunosuppressive pharmaceutical compounds such as anti-TNF agents [8] or thiopurine agents [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, steroid administration can increase susceptibility to infections, diabetes mellitus and osteoporosis. Recently, it was reported that steroidrefractory or steroid-dependent patients with UC can be effectively treated by cytapheresis [7][8][9][10] . To determine whether leukocytapheresis (LCAP) may also be useful with other UC patients, we administered LCAP to 18 steroid-naive UC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently in a randomized pilot trial, 20 patients with active UC not responding to conventional treatment received Cellsorba apheresis treatment, 1 session/week for 5 consecutive weeks [67]. Of 20 patients, 14 achieved clinical remission and 6/20 patients also achieved endoscopic remission.…”
Section: Cellsorba Leukocytapheresis For Ulcerative Colitismentioning
confidence: 99%
“…The 14 responder patients were further randomized to receive a monthly apheresis session or no further treatment. After 6 months, 5/8 patients receiving monthly apheresis maintained remission compared to 1/6 in the group with no further treatment [67]. …”
Section: Cellsorba Leukocytapheresis For Ulcerative Colitismentioning
confidence: 99%